The Mediation/Moderation Effects of Gut Microbiota on Sleep Quality and Primary Liver Cancer: A Mendelian Randomization and Case–Control Study - Yang Y; Wang J; Su Q; Yang J; Bo Z; Zheng C; Xie Y; Chen K; Wang J; Chen G; Wang Y (Nature and Science of Sleep, 2024)
Yi Yang,1 Jingxian Wang,1 Qing Su,1 Jinhuan Yang,2,3 Zhiyuan Bo,2,3 Chongming Zheng,2,3 Yitong Xie,2,3 Kaiwen Chen,2,3 Juejin Wang,1 Gang Chen,2,3 Yi Wang1 1Department of Epidemiology and Biostatistics, School of Public Health, Wenzhou Medical University, Wenzhou City, Zhejiang Province, People’s Republic of China; 2Department of Hepatobiliary Surgery, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou City, Zhejiang Province, People’s Republic of China; 3Key Laboratory of Diagnosis and Treatment of Severe Hepato-Pancreatic Diseases of Zhejiang Province, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou City, Zhejiang Province, People’s Republic of ChinaCorrespondence: Yi Wang, Department of Epidemiology and Biostatistics, School of Public Health, Wenzhou Medical University, Nanliu Road, Chashan Street, Ouhai District, Wenzhou City, Zhejiang Province, 325035, People’s Republic of China, Fax +86(577)-86699-358, Email wang.yi@wmu.edu.cn Gang Chen, Department of Hepatobiliary Surgery, The First Affiliated Hospital of Wenzhou Medical University, Shangcai Village, Nanbaixiang Street, Ouhai District, Wenzhou City, Zhejiang Province, 325035, People’s Republic of China, Fax +86(577)-55579-555, Email chen.gang@wmu.edu.cnBackground: Primary liver cancer (PLC) is a fatal malignancy, sleep quality and gut microbiota were shown to be associated with PLC. However, the mechanism of how sleep quality affects PLC is unclear. This study aims to investigate the mediation/moderation effects of gut microbiota on sleep quality and the occurrence of PLC.Methods: The causality of sleep quality and the occurrence of PLC was detected through the Mendelian randomization (MR) analysis based on the data including 305,359 individuals (Finland Database) and 456,348 participants (UK Biobank). The primary method used for MR analysis was inverse-variance weighted analysis. Gut microbiota’ mediation/moderation effects were uncovered in the case–control study including 254 patients with PLC and 193 people with benign liver diseases through the mediation/moderation effect analyses. People’s sleep quality was evaluated through the Pittsburgh sleep quality index (PSQI).Results: Poor sleep quality could lead to PLC through the MR analysis (P = 0.026). The case–control study uncovered that Actinobacteria had mediation effects on the relationship between PSQI score, self-sleep quality, and the occurrence of PLC (P = 0.048, P = 0.046). Actinobacteria and Bifidobacterium could inhibit the development of PLC caused by short night sleep duration (P = 0.021, P = 0.022). Erysipelotrichales could weaken the influence of daytime dysfunction on PLC (P = 0.033). Roseburia modulated the contribution of nocturnal insomnia and poor sleep quality to PLC (P = 0.009, P = 0.017).Conclusion: Poor sleep quality was associated with PLC. Gut microbiota’ mediation/moderation effects on poor sleep quality and the occurrence of PLC prompted an insightful idea for the prevention of PLC.Keywords: primary liver cancer, sleep quality, gut microbiota, Mendelian randomization, mediation/moderation effect